Performance and Applications of Pervious Concrete Pavement Material as an Overlay on Existent Concrete Slabs. Issue 3 (February 2019) - Bonicelli, Alessandra; Pianeta, Lorena Rico
Abstract: Portland Cement Pervious Concrete (PCPC) is a quite innovative type of concrete that has woken up the interest of the academy and construction field due to its economic, social and environmental advantages. PCPC is composed by coarse aggregate, little or no fine aggregate, a reduced water/cement ratio and additives. In consequence to its lack of fine aggregate, PCPC has high porosity and lower strength in comparison with traditional concrete, thus its main applications are in low traffic areas such as parking lots, sidewalks, residential streets, path in natural areas. Within its benefits stand out the simplification of drain system, the management of storm water runoff and the reduction of pavement infrastructure costs. Pervious concrete pavement is worldwide recognized for its environmental benefits; the use of pervious concrete for urban pavements produce a reduction of traffic noise, as well as the water and soil pollution, it allows the natural recharge of the groundwater and helps in limiting the heat island effect, due to its clear surface and permitting the soil transpiration. In the very few years a new application of this material has been implemented: pervious concrete layer as an overlay over existing concrete slab. The resulting pavement structure may be used for high traffic volume roads, thanks to the support of the stiff concrete slab, with the addition of the benefits of the optimal pervious concrete surface characteristics. In the present investigation work, design methodologies, construction techniques, laboratory measurements and long term evaluations of this innovative material are presented. Pervious concrete has proven to have a broad scope and a promising future for the research of eco-friendly materials for the construction of pavements throughout the world. In conclusion, the case of study of the application of a pervious concrete overlay in an airport infrastructure is proposed. In particular, the pavement structural behaviour was studied and verified for determining the suitability for solving drainage problems in an aircraft parking lot.